Adoption of cloud computing tools for sustainable construction: a structural equation modelling approach - Oke, A.E. (Emerald Group Holdings Ltd., 2022)
Purpose: The purpose of this paper is to assess the cloud computing (CC) methods and tools towards the achievement of construction project sustainability in Nigeria. Design/methodology/approach: Data were obtained from the literature, complemented by a quantitative method using a questionnaire distributed among 104 respondents comprising mainly construction professionals in Nigeria. Subsequently, data were analysed using the exploratory factor analysis (EFA) method. In addition, the partial least square structural modelling was used to generate a model for the adoption of CC tools for sustainable construction. Findings: EFA results indicated that the CC implementation tools could be categorised into four significant constructs: platform, communication, software and data storage. Results obtained from the model showed that platform tools were the most crucial tools for implementing CC in the construction industry. Practical implications: The findings from this study are essential to the pursuit of perception of methods and tools connected to the vagueness of CC for future employees. In addition, the identified CC tools are expected to enhance the success of construction projects. Originality/value: The novelty of this research work will be a benchmark or board for decision-makers to quality by adopting CC methods and tools in Nigeriaâs construction projects to achieve their sustainable projects. Â© 2021, Emerald Publishing Limited.